Coastal Towns in Transition: Local Perceptions of Landscape Change - Green, Raymond James. (Springer Netherlands, 2010)
Many coastal areas around the world are experiencing dramatic landscape changes as a result of increased tourism development and the "sea change phenomenon" the migration of affluent urbanites to small coastal towns seeking beautiful, natural surroundings. In response to these changes local residents in these places often complain that the distinctive character of their towns and/or individual neighborhoods is being lost or degraded. Coastal Towns in Transition looks at how changes due to unsympathetic development of the built environment and modification of the natural landscape are perceived to negatively impact on the character of small coastal towns. The book explores the concept of town character, and associated notions of sense of place, genius loci and place identity, as conceptualised by local residents in several coastal town communities along Australias Great Ocean Road. Findings of a four-year study involving over 1800 respondents from these communities are used to explore theoretical and methodological issues associated with the assessment of place character in the context of coastal towns that are experiencing rapid environmental change. This book will be of interest to planners and environmental designers, as well as scholars in both landscape studies and social science and planning fields who are interested in the sustainable development of coastal areas. The case studies and associated planning and design strategies, together with the bibliography of selected relevant literature, will provide an invaluable reference for these scholars.